Biomechanical evaluation of six zygomatic implants versus four zygomatic implants combined with dental implants in the treatment of different maxillary defects - Zeynep Gümrükçü; Emre Balaban; Zeynep Bayramoğlu (BMC, 2024)
Abstract Background This study aims to compare the biomechanics of six zygomatic implants (ZIs) and dental implants (DIs) combined with four ZIs with different maxilla defects. Methods Three-dimensional constructs of the ZIs, DIs human skulls, and maxillary prostheses were created using SolidWorks Software (Version 2015, Dassault Systems SolidWorks Corporation, Waltham, MA, USA). Eight finite element models of the skull with four different alveolar defect types (0-4) were constructed. Type 0: No defect; Type 1: Bilateral posterior defects; Type 2: Right posterior defect; Type 3: Anterior and left posterior defects; Type 4: Bilateral posterior and anterior defects. In two models with the same defect type (for defect types 0-2), six ZIs or two DIs combined with four ZIs were inserted into the maxilla. Six ZIs were inserted in the maxilla models with defect types 3 and 4. Vertical (150 N) and masseteric (300 N) loads were simulated on the prosthesis. The maximum Von Mises stress in the implants/surrounding bone and bone deformation were evaluated. Results The maximum Von Mises stresses in bone/implant were found highest in the defect type 2 model with four ZIs combined with two DIs. The lowest maximum Von Mises stress for bone was detected in the model with defect type 0 and with six ZIs. Conclusion Among the four types of defects, the posterior unilateral defect caused the highest stress value.